Lake Evolution in the Żnin Region in the Years 1912– 1960 (Central Poland) - Ptak, Mariusz (Quaestiones Geographicae, 2013)
The evolution of lakes, which, in the final stage, leads to their disappearance, is mainly based on the analysis of surface area change. However, there is one more, frequently overlooked process, which determines lake disappearance - namely the lake shallowing. The present paper presents the direction and rate of such evolution, taking both these processes into account. It is a comparative analysis of 9 lakes in the Żnin region - which has the greatest water deficit in the whole of Poland. Based on bathymetric plans from two periods (early 20th century and early 60’s of the 20th century), the author was able not only to evaluate the scale of surface area change but also to determine the value of lake basins volume change. Both these values were negative and amounted 9.1% and 14.9% respectively. Assuming that the said processes are invariable, the prospective period of lake functioning is about 500 years when taking into consideration surface area change only, and is 150 years shorter when allowing for aquatic resources change. The presented approach to lake disappearance analysis, which treats this phenomenon as a decline in aquatic resources rather than a simple decrease in surface area, is more reliable and therefore, scientific works in this field should take the results of lake shallowing into consideration.